LINGKUNGAN KELUARGA SEBAGAI WAHANA SOSIALISASI DAN INTERAKSI EDUKATIF BAGI ANAK (SUATU TINJAUAN SOSIO-EDUKASI RELIGIUS TERHADAP PENDIDIKAN DALAM KELUARGA) - GUSTINA GUSTINA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
Family environment is the first and the main medium for socialization. Maintaining children’s welfare is the basic foundation to achieve daily effective life. Such welfare can be achieved through qualified education where religious educative interaction among the family members. The techniques can be done by means of approaches, such as parents should plan what to say, not in a hurry, be open and be honest to themselves and the children as well. Among the approaches are: 1) open dialog with cildren, 2) critical and creative thinking, and 3) value clarification. Parents, therefore, need to: 1) apply moderate mode of education to their children, 2) create intimate atmosphere among parents and children, 3) familiarizing the children with the feeling of guilty, and 4) provide a wide range of opportunity to interact and socialize with their neighborhood in positive sense.Kata Kunci: pendidikan, lingkungan keluarga, sosialisasi, interaksi edukatif, sosio-edukasi religius